Developing Children’s Ability to Read the Qur’an with the Qiro’ati Method - Fitriana, Aida; Hidayatulloh ZC, Mohammad Syarif (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2025)
Qur’an Education Park (TPQ) acts as a solution to improve Qur’an literacy among children who have limited access to formal religious education by implementing a systematic Qiro’ati method and emphasizing the use of tajwid from the beginning of learning. This study aims to examine the application of the Qiro’ati method at TPQ. H. Achmad Ali and to explore the efforts made by teachers in developing children’s Qur’an reading skills with the Qiro’ati method. The method used in this study is descriptive qualitative, with research subjects including the head of TPQ, teachers, and students. Data were collected through observation, interviews, documentation, and literature studies. The results of the study showed that teachers made various efforts to develop students’ Qur’an reading skills through the application of the Qiro’ati method at TPQ, namely providing examples of how to read the Qur’an with tartil and clearly, listening to readings individually, approaching through the pre-volume method, providing repetition material, habituating reading the Qur’an continuously, packaging learning with interesting games, providing motivation, reading additional material during rows, and holding coaching for teachers. This research contributes to providing practical insights into the implementation of the Qiro’ati method at the local level so that it can be a reference for other TPQs in increasing the effectiveness of learning to read the Qur’an.